The Effects of Teacher Professional Development on Teaching Practice and Student Learning Outcome - Duy, Truong Bao (EDUCARE, 2015)
ABSTRACT: Professional development is of great importance not only for teachers but also for administrators and leaders. It helps teachers improve or change their teaching behaviors and make their lessons more interesting and effective. To meet the academic needs of learners, it is clear that schools need to build seasoned and well-qualified teaching staff. It is commonly agreed that with the same modern facilities, only the upgrade of teaching quality sets themselves apart from any other schools. The purpose of this study was to investigate the effects of teacher professional development activities attributed to teaching and learning skills acquired as well as to determine teacher attitude toward their participation in these activities. About 114 teachers participated in the study. The data collected from the returned questionnaires were entered into the computer file using Microsoft Excel for the analysis. The study answered the following research questions: (1) What are the teachersâ perceptions toward professional development activities they have participated in?; (2) To what extent do trained teachers implement what they have learned?; and (3) What do teachers suggest for professional development training activities? The findings show that teachers have positive perceptions toward professional development training and they hope to attend more trainings in the future. Regarding teachersâ application of new learning in the classrooms, school leaders should invite facilitators who are experienced in teaching the same materials that respondents teach. The facilitators can take examples from the materials. In this way, respondents can find skills and techniques applicable. They also can change their teaching behaviors and classroom activities.KEY WORDS: Professional development, teaching activities, teaching capacity, teachersâ perception, teaching practice, training program, and student learning outcome.About the Author: Truong Bao Duy is a Manager, Department of International Development SEAMEO RETRAC (South-East Asian Ministers of Education Organization, Regional Training Center), 35 Le Thanh Ton Street, District 1, Ho Chi Minh City, Vietnam. For academic intetests, the author can be contacted via phone at: (84.8) 38245618 or via e-mail at: tbduy@vnseameo.orgHow to cite this article? Duy, Truong Bao. (2015). âThe Effects of Teacher Professional Development on Teaching Practice and Student Learning Outcomeâ in EDUCARE: International Journal for Educational Studies, Vol.7(2) February, pp.181-188. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (November 21, 2014); Revised (December 29, 2014); and Published (February 28, 2015).